Determination of optimal charge parameters on reactive magnetron deposition of NbN films. Opredelenie optimal'nykh parametrov razryada pri reaktivnom magnetronnom napylenii plenok NbN - "Gol'man, E K"; "Zajtsev, A G" (1992)
The aim of the work is to show that optimal parameters of NbN film deposition can as well be determined by the dependence of coating deposition rate on the pressure of argon-nitrogen mixed gas. Characteristic dependences of coating deposition rate (V) on the working gas pressure, measured under niobium target sputtering in pure argon and in the mixture of Ar and 25% of N[sub 2] are presented. The discharge power is kept at the level of 900 W. It is ascertained that under arbitrary choice of discharge power value and Ar-N[sub 2] mixture composition comparison of V(P) dependences measured under Nb target sputtering in Ar mixture allows one to unambiguously determine the interval of the mixture pressures providing for the production of high-quality superconducting NbN films.
Keywords: "36 MATERIALS SCIENCE"; "NIOBIUM NITRIDES"; "FILMS"; "ARGON"; "MAGNETRONS"; "PRESSURE DEPENDENCE"; "SPRAYED COATINGS"; "SURFACE COATING"; "COATINGS"; "DEPOSITION"; "ELECTRON TUBES"; "ELECTRONIC EQUIPMENT"; "ELEMENTS"; "EQUIPMENT"; "FLUIDS"; "GASES"; "MICROWAVE EQUIPMENT"; "MICROWAVE TUBES"; "NIOBIUM COMPOUNDS"; "NITRIDES"; "NITROGEN COMPOUNDS"; "NONMETALS"; "PNICTIDES"; "RARE GASES"; "REFRACTORY METAL COMPOUNDS"; "TRANSITION ELEMENT COMPOUNDS"; "360201* - Ceramics, Cermets, & Refractories- Preparation & Fabrication"